2006
DOI: 10.1002/hipo.20240
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus is required for short‐term topographical memory in humans

Abstract: ABSTRACT:The hippocampus plays a crucial role within the neural systems for long-term memory, but little if any role in the short-term retention of some types of stimuli. Nonetheless, the hippocampus may be specialized for allocentric topographical processing, which impacts on short-term memory or even perception. To investigate this we developed performance-matched tests of perception (match-to-sample) and shortterm memory (2 s delayed-match-to-sample) for the topography and for the nonspatial aspects of visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
337
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(362 citation statements)
references
References 100 publications
24
337
1
Order By: Relevance
“…Equally, the right hippocampal representation of allocentric spatial location has long been argued to be an important component of the representation of context within episodic memory (1, 3-5, 9). This representation is also consistent with studies implicating the hippocampus [often specifically on the right (10,41)] in flexible representation of environmental topography (3,46), accurate large-scale navigation (41), and memory for arrays of locations when containing large numbers of objects (10,19) or tested from a shifted viewpoint (19).…”
Section: Discussionsupporting
confidence: 85%
“…Equally, the right hippocampal representation of allocentric spatial location has long been argued to be an important component of the representation of context within episodic memory (1, 3-5, 9). This representation is also consistent with studies implicating the hippocampus [often specifically on the right (10,41)] in flexible representation of environmental topography (3,46), accurate large-scale navigation (41), and memory for arrays of locations when containing large numbers of objects (10,19) or tested from a shifted viewpoint (19).…”
Section: Discussionsupporting
confidence: 85%
“…Here, too, we localised HC using a working memory task, thus complementing previous studies that find evidence for HC recruitment across a range of cognitive tasks. Indeed, several studies of patients with HC atrophy have reported scene‐specific deficits for both memory and perceptual tasks [Bird et al, 2008; Hartley et al, 2007; Lee et al, 2005a, 2005b; Mullally et al, 2012; but see Kim et al, 2011, 2015]. Functional neuroimaging studies have likewise found group‐level HC activation during scene discrimination [Aly et al, 2013; Lee et al, 2008], scene construction/imagining [Zeidman et al, 2015], and working memory [Lee and Rudebeck, 2010b; Park et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the seminal work in both rats and non‐human primates—which identified HC cells attuned to allocentric location [O'Keefe and Nadel, 1978] and spatial view [Rolls, 1999]—recent models of human medial temporal lobe (MTL) function highlight the HC as an important structure for scene processing, via a proposed role in representing complex and conjunctive scene stimuli [Graham et al, 2010; Lee et al, 2012; Murray et al, 2007] and/or by contributions to viewpoint‐independent scene construction [Bird and Burgess, 2008; Maguire and Mullally, 2013; Zeidman et al, 2015]. These complex HC scene representations have been shown to support behavioural performance across a range of cognitive domains, including recognition memory [Bird et al, 2008; Taylor et al, 2007], short‐term memory [Hannula et al, 2006; Hartley et al, 2007], working memory [Lee and Rudebeck, 2010a, 2010b; Park et al, 2003], perceptual learning [Mundy et al, 2013], higher‐order perception [Aly et al, 2013; Barense et al, 2005, 2010; Kolarik et al, 2016; Lee et al, 2005b] and scene imagination [Hassabis et al, 2007]. …”
Section: Introductionmentioning
confidence: 99%
“…There has also been interest in the idea that the MTL, and the hippocampus in particular, might have a special role in spatial processing beyond its established role in memory (4,5). Several studies have reported that patients with damage to the MTL were impaired in various kinds of spatial tasks, even when the burden on memory appeared quite small and when tasks of nonspatial memory appeared less affected (6)(7)(8)(9).…”
mentioning
confidence: 99%